TRENDS OF CLIMATIC ELEMENTS IN THE SEMI-ARID REGION OF BRAZIL: CASE STUDY OF CARIRI PARAIBANO - Salvador, Maria do Socorro Silva; Lucena, Daisy Beserra; de Souza, Bartolomeu Israel; Sampaio, Tony Vinícius Moreira; Borges Neto, Inocencio de Oliveira (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
The Cariri region of Paraiba, located in the semi-arid region of Northeast Brazil, is a region characterized by high temperatures, great irregularity in the spatio-temporal distribution of precipitation, and long periods of drought. These conditions generally exert a strong influence on the local agriculture-based economy. With an expected increase in extreme events, it is crucial to study the distribution of precipitation and temperatures. Therefore, this study aims to analyze temporal patterns of precipitation and temperature in the municipalities of Monteiro and São João do Cariri, seeking to identify trends in the historical series. Precipitation and temperature data were used and the non-parametric Mann-Kendall, Sen’s, and Pettitt tests were applied. The results indicated a statistically significant trend in the annual and monthly temperature data (in the months of May, April and June) for Monteiro, whereas this condition was not observed for the precipitation of the localities under analysis. As for the ruptures identified with Pettitt’s method in the annual series of precipitation and temperature observed, these occurred, respectively, for Monteiro in the years 1999 and 1997 and in São João do Cariri in the years 2011 and 2009. Thus, although the municipalities present a similar climatic pattern, the trends identified were only detected in the temperature for Monteiro. Therefore it is of fundamental importance to carry out more studies covering the entire area of Cariri Paraibano, since comprehensive knowledge will facilitate the understanding of the specific needs of each municipality in the face of climate impacts